2023
DOI: 10.1097/mco.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

The use of commercial wrist-worn technology to track physiological outcomes in behavioral interventions

Abstract: Purpose of review The aim of this review is to provide an overview of the use of commercial wrist-worn mobile health devices to track and monitor physiological outcomes in behavioral interventions as well as discuss considerations for selecting the optimal device. Recent findings Wearable technology can enhance intervention design and implementation. The use of wrist-worn wearables provides the opportunity for tracking physiological outcomes, thus provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that 2 days of monitoring were sufficient to obtain good reliability in estimating daily steps, as indicated by an intraclass correlation coefficient (ICC) (2,1) > 0.9. Notwithstanding, ankle-mounted devices are generally less tolerated by users [37,38] compared with wrist-worn sensors [37,39,40] and research-grade devices are usually expensive, less available on the market, and require a higher level of expertise to be used [19], thus limiting their application. To this end, the use of commercial, wrist-worn devices, such as smartwatches, could help disseminate this technology and increase the possibility of monitoring walking at home.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that 2 days of monitoring were sufficient to obtain good reliability in estimating daily steps, as indicated by an intraclass correlation coefficient (ICC) (2,1) > 0.9. Notwithstanding, ankle-mounted devices are generally less tolerated by users [37,38] compared with wrist-worn sensors [37,39,40] and research-grade devices are usually expensive, less available on the market, and require a higher level of expertise to be used [19], thus limiting their application. To this end, the use of commercial, wrist-worn devices, such as smartwatches, could help disseminate this technology and increase the possibility of monitoring walking at home.…”
Section: Introductionmentioning
confidence: 99%